PENERAPAN “KNOWLEDGE SHARING” DALAM KEGIATAN “OVERNIGHT STAY AT LIBRARY” BERSAMA PEGIAT LITERASI DI SUMATERA BARAT: Studi Kasus Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Fatma , Riska (UIN Imam Bonjol Padang, 2022)
Awareness of the importance of information and knowledge is felt by individuals because of the need that is always driven by information. Knowledge is an important asset to improve abilities and survival skills in dynamic activities. The emergence of various communities or movements such as literacy activists in the library aims as an effort to become a learning community in utilizing information into useful knowledge for people's lives. This article discusses the implementation of